A phenomenological study of the experience of pathological pain in individuals undergoing Spontaneous Healing Intrasystemic Process (SHIP®) therapy - Prinsloo, A. (Adri) (University of Pretoria, 2013)
Dissertation (MA (Psychology))--University of Pretoria, 2008.